FACTORS CONTRIBUTING TO PENDING INPATIENT CLAIMS IN THE NATIONAL HEALTH INSURANCE PROGRAM: A SYSTEMATIC LITERATURE REVIEW - Mertisa Dwi Klevina; Irmawati Mathar (Jurnal Penelitian Progresif, 2026)
Indonesia’s National Health Insurance program (Jaminan Kesehatan Nasional, JKN) applies the INA-CBGs payment system for inpatient services to improve efficiency and cost containment. However, hospitals frequently experience pending inpatient claims, resulting in delayed reimbursement by BPJS Kesehatan and potential disruptions to hospital operations and financial sustainability. Existing studies examining pending claims are largely fragmented and context-specific, highlighting the need for a comprehensive synthesis of available evidence. This study aimed to systematically review and synthesize empirical evidence on factors contributing to pending inpatient claims within the JKN system and to develop evidence-based recommendations for improving claim management. A systematic literature review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were performed in PubMed, Scopus, Google Scholar, and Garuda databases for studies published between 2014 and 2025. Quantitative, qualitative, and mixed-methods studies conducted in Indonesian hospitals that examined causes or determinants of pending inpatient claims were included. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. A total of nine eligible articles met the inclusion criteria and were synthesized using narrative and thematic analysis, (Amanda & Sonia, 2023). The review of nine studies demonstrated that pending inpatient claims arise from multiple interrelated factors. Administrative issues, particularly incomplete and inconsistent claim documentation, were the most frequently reported causes. Technical and clinical factors—such as discrepancies in diagnosis and procedure coding and incomplete medical records—also played a significant role. Human resource-related factors, including limited coder competency, insufficient training on INA-CBGs, and high workload, further increased the likelihood of claim errors. In addition, limitations in hospital information systems and inadequate integration with BPJS Kesehatan claim platforms contributed to delays in claim verification. Pending claims were consistently reported to adversely affect hospital cash flow, operational efficiency, and service continuity. Pending inpatient claims within the JKN system represent a persistent and systemic challenge across Indonesian hospitals. Findings from the nine reviewed studies indicate that reducing pending claims requires integrated improvements in administrative processes, coding accuracy, medical record completeness, human resource capacity, and health information system integration. Strengthening internal claim audits, continuous staff training, and effective coordination between hospitals and BPJS Kesehatan are essential strategies to mitigate the occurrence of pending inpatient claims.